Graphological Deviation: A Defamiliarizing Trope in Timothy Wangusa’s Poetry - Evaristo, Arineitwe (East African Journal of Arts and Social Sciences, 2023)
This article attempts to examine the use of graphological deviation in Timothy Wangusa’s poetry as a style of foregrounding in Timothy Wangusa’s poetry. It is hoped to fill knowledge gaps in the Wangusaic scholarship as previous studies on Wangusa are on issues of originality of his poetry and conclude that the trajectory of his poetry is mainly Christian, African, and English traditions. The studies conclude that Wangusa’s poetry was greatly influenced by classical and western literary traditions (Alfredo Okello 2005). Some studies are on Wangusa’s novels and short stories, and as such, they focus on aspects like themes and narrative techniques but not graphological deviation. This leaves much to be studied on the variable of graphological deviation in Wangusa’s poetry. This justifies why this research article is worthwhile as it evaluates how Timothy Wangusa employs graphological deviation to create foregrounding. Besides, the researcher used the theory of defamiliarisation proposed by Viktor Shyklovsky throughout the study. The theory emphasises the use of poetic devices, which makes it an apt one as this study is on graphological deviation (which is used as a poetic device to achieve emphasis/foregrounding). The researcher used a textual analysis method and a descriptive research design in an attempt to explicate and make sense of the variable of graphological deviation. The results and findings from the data analysis prove that Wangusa uses graphological deviation to emphasise his message, shock or surprise readers (estrangement) and create mood in his poetry. This study recommends that studies be carried out on Timothy Wangusa’s use of deviation of register